The role of the University in skills recognition in continuing education programmes. An experience at the University of Catania - Roberta Piazza; Simona Rizzari (Firenze University Press, 2018)
This contribution focuses on the role of the University in promoting recognition of competences acquired in Continuing Education (CE) activities. The paper shows some results of a learning path that the University of Catania has developed since 2012 till 2018. Despite the lack of Regional laws regulating recognition of competences in Sicily, the University, through the Centre for continuing education and technology transfer (Capitt), has designed and implemented a set of procedures and tools aimed at building a process for assessment and certification of competences of workers involved in CE courses. This model allowed adults involved in CE courses to spend their competences in multiple contexts. Therefore the University of Catania has contributed to the training needs of the region, fulfilling its Third Mission tasks.   Il ruolo dell'università nel riconoscimento degli apprendimenti nei contesti di formazione continua. L'esperienza dell'Università di Catania Il contributo focalizza l'attenzione sul ruolo dell'Università nel favorire i processi di certificazione delle competenze acquisite nei contesti di formazione continua. Vengono presentati i risultati di un'esperienza realizzata dall'Università di Catania dal 2012 al 2018. In assenza di una normativa regionale di riferimento, l'Ateneo, attraverso il centro di servizi Centro per l'aggiornamento delle professioni e per il trasferimento tecnologico (Capitt), ha sviluppato, in via sperimentale, un insieme di procedure e di strumenti per la costruzione di un sistema di riconoscimento e di certificazione delle competenze dei lavoratori impegnati in attività di aggiornamento professionale, consentendone la spendibilità in molteplici contesti. In tal modo l'Università ha contribuito ai bisogni formativi del territorio, assolvendo ai compiti di Terza missione che le sono propri.